Comparison of DIPSI guidelines versus conventional OGTT for diagnosis of gestational diabetes mellitus - Desai, Grishma Girish; Sonawane, Pundalik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Gestational Diabetes Mellitus (GDM) is defined as carbohydrate intolerance with recognition or onset during pregnancy is associated with a higher rate of maternal and fetal compromise. OGTT is the current gold standard for screening for GDM. It is a two-step test which requires the pregnant woman to be in a fasting state for a long duration. DIPSI is a one-step procedure for diagnosing GDM does not require patients in a fasting state and is a simple, economical and feasible alternate in Indian scenario. The aim of this study is to compare DIPSI criteria-based test with conventional OGTT for diagnosis of GDM. Methods: A hospital-based screening study was conducted at Department of Obstetrics and Gynecology, K J Somaiya Medical College and hospital, Mumbai for duration of May 2015 to June 2016. A total of 200 consecutive pregnant women in the second and third trimester of pregnancy registered at our antenatal clinic and satisfying the eligibility criteria were taken in the study after informed consent. Pregnant women with 2-h PG ≥ 7.8 mmol/L (DIPSI criterion) were diagnosed as GDM and rest were classified as normal glucose tolerant (NGT) women. One week later all of them were made to undergo the conventional 75 gm OGTT. Data was analyzed using statistical software SPSS ver. 21. Results: The sensitivity and specificity of DIPSI was 86.8% and 98.8% with PPV and NPV of 94.3% and 97.0% and overall diagnostic accuracy was 96.5%. Conclusions: The results of present study show that DIPSI is a simple, single, convenient, economical screening test for GDM and can be used as both diagnostic as well as screening test with good diagnostic efficacy.